Petrogenesis and tectonic setting of the Bondla mafic-ultramafic complex, western India: Inferences from chromian spinel chemistry. (15th November 2016) - Ishwar-Kumar, C.; Rajesh, V.J.; Windley, B.F.; Razakamanana, T.; Itaya, T.; Babu, E.V.S.S.K.; Sajeev, K.
Graphical abstract: Highlights: Detailed study of chromian spinel chemistry from Bondla ultramafic-mafic complex. Estimation of rock crystallization P-T conditions using mineral compositions. Melt calculations suggests parental magma similar to modern primitive tholeiitic basalt. Chromian spinel chemistry suggests supra-subduction zone-arc tectonic setting. Evolution of the Bondla arc attributed to the formation of the Kumta suture. Abstract: Crustal-scale shear/suture zones hold prime importance because they are one of the critical parameters used for paleogeographic configurations of supercontinental assemblies. The Kumta suture, located on the western margin of peninsular India, has been interpreted as the eastern extension of the Betsimisaraka suture zone of Madagascar. This suture separates the Karwar block ( ca. 3200 Ma tonalite-trondhjemite-granodiorite (TTG) and amphibolite) in the west from a quartzite-dominated shelf that overlies ca. 2571 Ma quartzo-feldspathic gneisses of the Dharwar block in the east. The NW/SE-trending Bondla ultramafic-mafic complex, situated in the arc just west of the Kumta suture, comprises gabbro, troctolite, wehrlite, dunite, peridotite, pyroxenite, chromitite and chromian spinel-bearing serpentinite. In this paper, we study the chemistry of Cr-spinels in chromitites and serpentinites to help understand their paleo-tectonic environments. The Cr-spinel in Bondla chromitites and serpentinites shows variations in Cr# [Cr/(Cr + Al)] ranging from 0.54 to 0.58 and 0.56 to 0.64 respectively; also, the Mg# [Mg/(Mg + Fe)] varies from 0.56 to 0.67 and 0.41 to 0.63 respectively. The Cr-spinels in serpentinites have strong chemical zoning with distinctive ferrian chromite rims (Mg# 0.41–0.63), whereas the Cr-spinels in chromitites are generally homogeneous with only occasional weak zoning. The spinel-core crystallization temperature in the serpentinite is estimated to be above 600 °C (the spinel stability field was calculated for equilibrium with Fo90 olivine), which suggests the core composition is chemically unaltered. The Cr-spinels in all studied samples have low-Al2 O3 (15–23 wt%) and moderate to high-Cr# (0.54–0.69), suggesting derivation from a supra-subduction zone arc setting. The chemistry of clinopyroxene in serpentinite indicates a wide range of crystallization temperatures from 969 °C to 1241 °C at 1.0 GPa. The calculated parental magma composition was similar to that of a modern primitive tholeiitic basalt formed by a high-degree of mantle melting. We ascribe the formation of the subduction-generated Bondla arc to the closure of the ocean that led to the formation of the Kumta suture. Thus, chromian spinel chemistry proves to be a viable indicator that helps understand the thermal conditions and tectonic derivation of the Bondla ultramafic-mafic complex against a suture zone in western India.